Klasifikasi Penyakit Mata Pada Data OCT Menggunakan Convolutional Neural Network (CNN) - Fausta Vita Austrin; Jefri Danil; Rahmat Ibnu Iman; Meidina Rahmawati Putri; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Optical Coherence Tomography (OCT) is a non-invasive medical imaging technique used to diagnose various eye diseases, such as age-related macular degeneration, glaucoma, and diabetic retinopathy. In this study, we developed a Convolutional Neural Network (CNN) model to classify eye diseases on OCT data. Our CNN model consists of several convolution, pooling, and fully connected layers trained on an OCT dataset comprising 7 common classes of eye diseases. Further analysis reveals that the features learned by the CNN model effectively capture the visual characteristics that distinguish between different eye disease classes. We believe that the proposed CNN-based approach can be a useful tool for ophthalmologists to assist in the early and accurate diagnosis of eye diseases using OCT data.